Conventional genetic manipulation of desulfurizing bacteria and prospects of using CRISPR-Cas systems for enhanced desulfurization activity. (3rd May 2020) - Parveen, Sana; Akhtar, Nasrin; Ghauri, Muhammad A.; Akhtar, Kalsoom
Abstract: Highly active and stable biocatalysts are the prerequisite for industrial scale application of the biodesulfurization process. Scientists are making efforts for increasing the desulfurizing activity of native strains by employing various genetic engineering approaches. Nevertheless, the achieved desulfurization rate is lower than the industrial requirements. Thus, there is a dire need to use efficient genetic tools for precise genome editing of desulfurizing bacteria for enhanced efficiency. In comparison to the previously used genetic engineering tools the newly developed CRISPR-Cas is a more efficient and simple genetic tool that has been successfully applied for targeted genome modification of eukaryotes as well as prokaryotes. In this paper, we have reviewed the approaches, previously used to enhance the biodesulfurization rates of the sulfur metabolizing microorganisms and have discussed the potential of CRISPR-Cas systems in engineering desulfurizing biocatalysts. We have also proposed a model to construct competent desulfurizing recombinants involving use of CRISPR-Cas technology. The model can be used to over-express the dsz genes under a constitutive promoter in a suitable heterologous host, to get a steady expression of desulfurization pathway. This may serve as an inducement to develop better performing desulfurizing recombinant strains using CRISPR-Cas systems, which can be helpful in increasing the rate of biodesulfurization in future.